Virtual reality in heritage studies and historical reconstruction through animation – A case study of a 16th century university complex in the Ottoman world - Ibrahim, Mansor; Jahn Kassim, Puteri Shireen; Ali, Maisarah; Abdul Latif, Nurul Syala; Zainal Abidin, Nor Zalifa (2007)
The paper describes the research and development of a virtual project based on the visualisation of measured architectural and construction details and extended research into a heritage building i.e. a 16th century Islamic complex undertaken as part of an architectural curriculum subject entitled ‘Heritage studies’. The modelling was focused on selected portions of the Suleymaniye complex in Istanbul Turkey, while the animation and storyboard integrated findings from a research extension of the project which looked at the link between the social structure of the city with the overall hierarchical nature of the architecture and planning of the complex. Virtual reality and animation tools were used within the process of analysing the architecture and construction technology within the background of the social structure of the Ottoman society during 15th and 16th centuries. The aim was not only to deepen constructional understanding but to discover the historical and social context which lay behind the development of its city life. The virtual reality dimension of the study focused on a virtual walkthrough and animation of the overall Suleymaniye complex and selected parts of the complex such as the madrasa and the ‘imaret’ or soup kitchen. The focus of the virtual walkthrough is the Süleymaniye Mosque which is surrounded by four medreses, a Darulhadis Medrese which had specialized in teaching Hadith, a medical school, a primary school, a hospital, a reflection hall, a caravanserai, shops, bath house, imaret (soup kitchen), caravanserai (inn), darussifa (hospital) or the hammam covering a 7.3 hectares wide area. Virtual reality was further used to enhance the story board based on the study on the link between the ‘waqf’ or pious foundations, and development of Ottoman urban life with the ultimate aim of linking these complexes to the social system and structure of urban society.